Edukasi Kesehatan Pada Pemeriksaan Radiologi: Perspektif Pemeriksaan Radiografi Genu Dan Mammography Di Desa Tegorejo, Pegandon, Kendal, Provinsi Jawa Tengah - Lucky Restyanti Wahyu Utami; Aryadiva Nugrahaning Prayoga; Siti Rosidah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
One way to diagnose disease can be done by radiological examination. However, the lack of public knowledge regarding radiological examinations to diagnose disease makes people afraid of carrying out radiological examinations because of the radiation effects they may receive. The aim of the service activities carried out for women in the scope of empowering family welfare in Tegorejo Village, Pegandon, Kendal, Central Java Province is regarding education on radiological examinations to enforce disease diagnoses using the lecture method. It is hoped that this can increase public knowledge regarding radiological examinations, especially regarding genu radiographic examinations to diagnose osteoarthritis and mammography examinations to diagnose mammary carcinoma are expected to help reduce people's fear of radiological examinations. From this service activity, the result was an increase in knowledge regarding genu radiography examination to diagnose osteoarthritis by 94% and an increase in knowledge regarding mammography examination to diagnose mammary carcinoma by 97%.